The relationship between financial literacy, rational financing decision, and financial performance: an empirical study of small and medium enterprises in Makassar - Sohilauw, Muhammad Irfai; Nohong, Mursalim; Sylvana, Andi (Penerbit Universiti Kebangsaan Malaysia, 2020)
This research analyzes the effect of Financial Literacy, Rational Financing Decision, Financial Capital, and SME Financial Performance. A survey approach is used for data collection from a sample of financed SMEs in Makassar City. Using the cluster method technique and stratified random sampling, 279 samples are obtained and analyzed with Structural Equation Modeling with the AMOS Software. The results show that Financial Literacy significantly affects Rational Financing Decision and Financial Capital. Rational Financing Decision significantly affects Financial Capital. Furthermore, Financial Literacy and Capital significantly affects performance. Moreover, Rational Financing Decision does not significantly affect Financial Performance. The study shows that Financial Capital is not a Moderator variable in explaining the relationship between Financial Literacy and Rational Financing Decision with Financial Performance. This research implies that financial institutions should be careful in providing loans to SMEs.